À deriva: temporalidades no repertório de Paulinho da Viola (1965-1996) - Medeiros, Kenia Erica Gusmão (2019)
This thesis aims to study the repertoire of the composer and singer Paulinho da Viola. Their songs are the chosen sources and are analyzed mainly in their discursive aspects and to some extent in their sonorous characteristics. The notions and perceptions of temporality present in their songs are discussed in these pages and related to their own creation and popularization as time measures. The historical context of his productions and the identitary senses of his verses are also appreciated in this work, as well as his understanding of samba and its transformations over time are also an important part of this text. The lyrics of Paulinho sing the psychological time of his characters promote their articulation with dimensions of the natural, social and historical times. Among the many metaphors that the artist uses is highlighted in this thesis that of water. In his work water acquires different senses and represents movements of life. Its correlated terms such as seas, rivers, boats and sailors, among others are elements that deepen the temporalities sung by Paulinho flowing in reflections on the drift that represents the existence.